2021
DOI: 10.1055/s-0041-1735199
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Factor in Unexplained Infertility and Recurrent Implantation Failure

Abstract: Unexplained infertility (UI) and recurrent implantation failure (RIF) are diagnoses based on failed pregnancy attempts within current infertility treatment models. Both diagnoses are made when fertility is unexplained based on current diagnostic methods and has no clear cause; UI is diagnosed when testing is inconclusive, and RIF is diagnosed after three failed in vitro fertilization cycles. In both cases, interventions are often introduced without an understanding of the cause of the infertility, frequently l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Considering the well-established endometrial contribution to RIF, eSPC abnormalities are expected to be involved in generating a persistently abnormal functionalis layer. Unlike in RPL, the endometrium of women with RIF is proposed to be hostile and less receptive to embryo-attachment [ 18 , 34 , 35 ]. Studies have suggested that eMSCs express markers of endometrial receptivity, such as adhesion molecules.…”
Section: Endometrial Stem/progenitor Cells and Recurrent Reproductive...mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the well-established endometrial contribution to RIF, eSPC abnormalities are expected to be involved in generating a persistently abnormal functionalis layer. Unlike in RPL, the endometrium of women with RIF is proposed to be hostile and less receptive to embryo-attachment [ 18 , 34 , 35 ]. Studies have suggested that eMSCs express markers of endometrial receptivity, such as adhesion molecules.…”
Section: Endometrial Stem/progenitor Cells and Recurrent Reproductive...mentioning
confidence: 99%
“…[ 12 , 29 , 30 , 31 , 32 , 33 ] ( Figure 1 A). RIF is thought to be related to decreased endometrial receptivity [ 18 , 34 , 35 ] and RPL to an unselective or permissive endometrium with an impaired decidualisation, leading to disrupted embryo-endometrial dialogue, with a consequential lack of natural embryo selection and subsequent inappropriate implantation of a non-viable embryo [ 12 , 36 , 37 ]. Increasing evidence is now emerging that suggests a strong endometrial cause for RRF, with reports suggesting that two-thirds of RIF is secondary to inadequate endometrial receptivity [ 3 , 6 , 18 , 38 ], and many other studies also propose an association between unexplained RPL and a defective endometrium [ 3 , 6 , 17 , 32 , 39 ] ( Figure 1 B).…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is defined as the inability to conceive within a year of regular unprotected intercourse affecting one in six couples. The most common causes of infertility are ovulatory dysfunction, male factor infertility, and tubal disease [1]. Unexplained Infertility (UI) and Recurrent Implantation Failure (RIF) are diagnoses based on failed pregnancy attempts with current infertility treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…UI is the absence of conception despite 12 months of unprotected intercourse, not explained by anovulation, poor sperm quality, tubal pathology or other known cause of infertility. RIF is defined by three failed IVF cycles in which one or two high-quality embryos are transferred in each cycle or by two failures in oocyte donor recipients after the transfer of good quality embryos [1]. UI is a common cause of infertility affecting Citation: Harșa R, Pintea I, Micu R, Surcel M, Stamatian F. Evaluation of IL-1β and TNF-α level in endometrial flush in patients with recurrent implantation failure.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, some other studies highlighted that sperm DNA damage is not linked to ART outcome (Lin et al, 2008;Niu et al, 2011). This link is even more scarce in couples with unexplained infertility and recurrent implantation failure (RIF) (Santamaria & Sim on, 2021).…”
Section: Introductionmentioning
confidence: 99%